PROPERTIES OF WORDS, TERMS AND TERMS - Khosiyat Abduqahhorova (Bright Mind Publishing, 2025)
This article is dedicated to Uzbek words, terms, and terminology, as well as their correct usage. The article comprehensively analyzes terms, words, and terminology, as well as their specific features, using scientific sources in Uzbek and Russian. The use of specific methods of comparing terms, words, and terminology increases its scientific and practical significance.
Keywords: Terminology, lexeme, term, system, component, term element, semantics, term, morpheme, monosemantics, equivalent, expressive, denotation, connotation, homonym, synonym, antonym.